(untitled) (Texas Journal of Agriculture and Biological Sciences, 2024)
In this article, the pre-irrigation standing moisture of cotton is 75-80-70 in relation to LFWC, depending on the irrigation procedures of cotton varieties in the conditions of light sandy loam soils. compared to the version irrigated in the percent order, the bulk density improved by 0.02-0.03 g/cm3 , the porosity was 1.5-2.5% higher, the cotton yield was 1 per hectare compared to the irrigation method Information on the possibility of obtaining an additional crop up to 6-3.3 s/h is provided.